The Music Learning Management Model Development for Autistic Children - Kasetsomboon, Pemika; Rodsakan, Tepika; Soontorntanaphol, Nuttika (Journal of Information and Learning [JIL], 2025)
This research aims to develop a music learning management model for children with autism and to study the effects of its implementation. The research process consisted of three phases: studying and analyzing baseline data, developing the music learning management model, and testing and evaluating the implementation of the model. The sample consisted of 10 purposively selected autistic children aged 13–15 years from Songkhla Pattana Panya School. The research tools included a needs assessment questionnaire, in-depth interview guide, music learning management model for children with autism, lesson plans, and behavior observation forms for students during music learning. The statistical methods used in the research were percentage, mean, median, standard deviation, and inferential statistics for reliability and validity analysis. The research results revealed that the developed music learning management model for children with autism consisted of four main components: 1) principles, 2) objectives, 3) learning management processes, and 4) evaluation. The learning management model included the acronym M = Morphology (study of external structures), E = Elemental music (basic musical knowledge conveyed through hand signals), L = Learning Relationship (interpersonal relationships in learning), O = Ostinato (singing using simple melodies), D = Deftness (instrumental performance), I = Improvisation (creating spontaneous music), and E = Exchange Impression (sharing impressions of music learning). The model consisted of 12 learning management plans. The quality assessment showed consistency, with IOC above 0.5. The evaluation of the music learning management model showed that it helped children with autism gain knowledge and understanding of music and express themselves creatively through music. This was assessed through the students’ initial learning processes in both theoretical and practical aspects of music, with an average score of 3.00 out of 3. This result indicated an excellent level of performance.